A simulation study on the effects of dendritic morphology on layer V prefrontal pyramidal cell firing behavior - Psarrou, Maria; Stefanou, Stefanos S.; Papoutsi, Athanasia; Tzilivaki, Alexandra; Cutsuridis, Vassilis; Poirazi, Panayiota (Frontiers in Cellular Neuroscience, 2014)
Pyramidal cells, the most abundant neurons in neocortex, exhibit significant structural variability across different brain areas and layers in different species. Moreover, in response to a somatic step current, these cells display a range of firing behaviors, the most common being (1) repetitive action potentials (Regular Spiking - RS), and (2) an initial cluster of 2-5 action potentials with short ISIs followed by single spikes (Intrinsic Bursting - IB). A correlation between firing behavior and dendritic morphology has recently been reported. In this work we use computational modeling to investigate quantitatively the effects of the basal dendritic tree morphology on the firing behavior of 112 three-dimensional reconstructions of layer V PFC rat pyramidal cells. Particularly, we focus on how different morphological (diameter, total length, volume and branch number) and passive (Mean Electrotonic Path length) features of basal dendritic trees shape somatic firing when the spatial distribution of ionic mechanisms in the basal dendritic trees is uniform or non-uniform. Our results suggest that total length, volume and branch number are the best morphological parameters to discriminate the cells as RS or IB, regardless of the distribution of ionic mechanisms in basal trees. The discriminatory power of total length, volume and branch number remains high in the presence of different apical dendrites. These results suggest that morphological variations in the basal dendritic trees of layer V pyramidal neurons in the PFC influence their firing patterns in a predictive manner and may in turn influence the information processing capabilities of these neurons.